A Study on Tourism Development in the Rawa Aopa Watumohai National Park South Konawe District, Southeast Sulawesi Province - Siti Salmiatin; Sambas Basuni; Tutut Sunarminto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
The development of ecotourism, especially in the National Park is important to acquaint the potential of nature in the National Park as the object of ecotourism activities. The purposes of this study were to describe and to asses the potential attractions and patterns of travel demand in Rawa Aopa Watumohai National Park (RAWNP), as well as to determine the direction of development ecotourism in RAWNP. Data collection were conducted in from December 2015 to February 2016, through field observation, interviews, literature study and questionnaires toward 30 respondents. Determining the potential attraction value was based on potential attraction criteria through scoring every aspect of the research study, beside that, gap analysis on this study is used to compare actual condition with expected condition and determine which is the gap between two conditions. The tourist attractions that had the highest scores are amboina orchid (Phalaenopsis amboinensis), knobbed hornbill (Ryticeros cassidix) and modus hill. Tourism demand in RAWNP shows that the greatest motivation for tourists is photography activities and birdwatching in savanna. The direction of future developments are product diversification, improvement of promotion, facilities and services as well as increase professionalism of human resources personnel.Keywords: attraction tourism, development of tourism, tourism demand